2022
DOI: 10.3390/ijerph19084844
|View full text |Cite
|
Sign up to set email alerts
|

Having a Say in Research Directions: The Role of Community Researchers in Participatory Research with Communities of Refugee and Migrant Background

Abstract: Research teams in high-income countries often fail to acknowledge the capacity and contributions of Community Researchers. This qualitative exploratory study used decolonising methodology and the Foundation House ‘Refugee Recovery Framework’ to understand Community Researchers’ perceptions and experiences of their role, and how research teams can integrate the knowledge they bring into research. Purposive sampling was used to facilitate the recruitment of eight Community Researchers from five different communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…This analytical framework was adopted to support a researcher’s interpretative, subjectivity, and deeper engagement with the study data in generating research knowledge [ 20 22 ]. In addition, previous studies involving data from ethnically diverse participants have used a thematic analytical framework partly to highlight differences and similarities in participants’ experiences [ 23 , 24 ]. The analytical strategy used in this study combined inductive and deductive approaches.…”
Section: Methodsmentioning
confidence: 99%
“…This analytical framework was adopted to support a researcher’s interpretative, subjectivity, and deeper engagement with the study data in generating research knowledge [ 20 22 ]. In addition, previous studies involving data from ethnically diverse participants have used a thematic analytical framework partly to highlight differences and similarities in participants’ experiences [ 23 , 24 ]. The analytical strategy used in this study combined inductive and deductive approaches.…”
Section: Methodsmentioning
confidence: 99%
“…Low levels of NIH investment in refugee health research may also be impacted by the lack of refugee representation among investigators or NIH reviewers or the lack of consideration of refugee investigators as minorities underrepresented in health sciences. Scientist-researcher pipeline programs may be useful in supporting investigators with lived refugee experience, who may have better access to target research populations to conduct this work in more professional capacities . Prior research has also identified a lack of diversity and expertise in health disparities research among reviewers in NIH peer review panels, which could contribute to the dearth of funding in this area .…”
Section: Discussionmentioning
confidence: 99%
“…Scientist-researcher pipeline programs may be useful in supporting investigators with lived refugee experience, who may have better access to target research populations to conduct this work in more professional capacities. 54 , 55 Prior research has also identified a lack of diversity and expertise in health disparities research among reviewers in NIH peer review panels, which could contribute to the dearth of funding in this area. 56 , 57 More work is also needed to understand how biases about refugees, influenced by negative media portrayal and political discourse around refugee populations, 13 may translate into fewer allocated funds and stricter restrictions for refugee health research.…”
Section: Discussionmentioning
confidence: 99%
“…Our research team includes researchers from the Muslim community, who have been involved with study design and will assist with facilitating the workshop. This is to ensure that the study is designed and conducted with an understanding of the dynamics of culture and language, as well as community trust and rapport 67. Participants will also be involved in decision-making regarding dissemination, particularly around whether to display body maps at a public exhibition.…”
Section: Methods and Analysismentioning
confidence: 99%
“…This is to ensure that the study is designed and conducted with an understanding of the dynamics of culture and language, as well as community trust and rapport. 67 Participants will also be involved in decision-making regarding dissemination, particularly around whether to display body maps at a public exhibition.…”
Section: Patient and Public Involvementmentioning
confidence: 99%